Evaluation of sulfate resistance of slag contained concrete under steam curing. (20th January 2019) - Yan, Xiancui; Jiang, Linhua; Guo, Mingzhi; Chen, Yunjie; Song, Zijian; Bian, Rui
Highlights: 70% slag improved the sulfate resistance of steam-cured concrete. 50% slag accelerated the sulfate damage of steam-cured concrete. Steam curing increased the deterioration of slag concrete. The variation of mass change lagged behind than that of open porosity. Abstract: This paper mainly investigated the sulfate resistance of the slag incorporated concrete under steam curing. Concrete samples with different replacement ratios (0%, 20%, 50% and 70%) of slag under steam curing were exposed to 5% Na2 SO4 solution for up to 540 days. Mass changes, open porosity and sulfate-ion contents of concrete were determined separately. Moreover, XRD, TGA, SEM and MIP were performed on the cement paste samples to investigate the landscape of their microstructures. The results showed that the variation of mass change lagged behind than that of open porosity. Steam curing increased the sulfate penetration and deterioration of the slag concrete. Interestingly, incorporation of 50% slag improved the sulfate resistance of standard-cured concrete and incorporation of 70% slag improved the sulfate resistance of steam-cured concrete. This was because a hydrotalcite type phase in the slag paste hindered the ettringite formation. However, the steam-cured concrete prepared with 20% and 50% slag experienced much worse deterioration, which was mainly due to the combined formation of ettringite and gypsum.